ANALISIS POLA ADAPTASI SOSIAL SISWA YANG MENGALAMI SELF INJURY DI SMA NEGERI 2 BANGUNTAPAN - Melansari, Intan; Prasetyoaji, Ari; Rahayu, Asri Puji (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Adolescence is often faced with an identity crisis in a period of self-discovery. Many teenagers commit self injury as an effort to vent their emotions so as not to lead to others. This of course needs to be analyzed the social adaptation patterns of adolescents who experience self injury in social or community life as students. This research aims to: 1) find out the negative social impact caused by self injury on students, 2) find out the motives of students doing self injury, 3) find out the social adaptation patterns of individuals as students who experience self injury. This study uses a qualitative research design using a descriptive approach. The research was conducted through observations and interviews with students who experienced self injury. From this study it was found that there are students as perpetrators of self injury who have difficulty interacting or just talking with peers because they are worried about social rejection. Efforts are also made by guidance and counseling teachers in overcoming the problem of self injury in students.